La evidencialidad en el discurso. Estableciendo los límites (2020)
Despite the extensive search that has been done on the phenomenon of evidentiality in the discourse, i.e. the coding of the information source, there are still terminological and conceptual discrepancies that need to be laid out. The present paper presents a theoretical framework of evidentiality. It starts with an examination of the scope of evidentiality in terms of grammar and semantics, ending up with a full understanding of the notion as a functional-conceptual domain. The discussion also focuses on the relationship between evidentiality and epistemic modality since this is still an open-ended issue in the field. We support that a thorough study of particular evidential forms, such as reportative evidential, would be needed as a vibrant continuation of this theoretical revision